Analysis of the Influence of Job Stress on the Job Engagement of Police Members in Operational Tasks in Region Y - Setiyaningsih, Sri Budhi; Rochmah, Fithri Nur; Prasetyo , Catur (Indonesian Scientific Publication, 2024)
Police should still have positive energy to improve the quality of work and be motivated to improve performance. However, some police cannot handle stress, so their work performance is not optimal, and even violations occur. This study examines the effect of work stress on work engagement for members of the National Police who are carrying out police operational duties. The approach used in this study is quantitative. We started the research step by collecting data, interpreting data, and presenting data results through statistical tests. The research method used is non-experimental with a prediction test, where this study aims to determine whether the independent variable influences the dependent variable. Google forms are used to fill out the scale and are completed by 250 police. The results of this study support Wasinis and Riyanto’s (2020) research, which assumes that stress affects work engagement, not the other way around. Stress affected work engagement for state police of the Republic of Indonesian members carrying out police operational duties. Based on the description of each research variable, the overall stress level and work engagement of participants tend to be high, and there is a demographic influence on the participants’ stress level and work engagement.